Japan’s Sharp Corporation: Aiming to boost its competitive edge (A) - SRIKANTH, Kannan (Institutional Knowledge at Singapore Management University, 2020)
Case A is set in 2010. Shinji Tanaka is a senior economist at Kyoto Heritage Foundation, a Japanese think tank, and he wondered if Sharp’s new manufacturing plant in Sakai could turn the company around. Sharp’s vision and innovative culture led it to invest in LCD technology. It played an important role in consigning cathode ray tube technology to the past and eventually outlasted plasma as well. However, Sharp’s fortunes started to take a hit as plant construction racked up large debts and profitability declined as the global economy shrank and LCD prices fell due to increased competition. The company responded by doubling down on LCD technology and built a larger and more expensive plant to build more technologically advanced LCD panels. Case B continues in 2016. Technological improvements continued to bring down the prices of LCD panels. Sharp had to be bailed out from its losses twice and was facing bankruptcy again. The company had to decide between two choices. One option was to merge with the Innovation Network Corporation of Japan (INCJ), a government-owned investment fund, to create a national champion. The second one involved doing a deal with Foxconn, a Taiwanese electronics giant that could realise synergies. Which option should Tanaka suggest Sharp to take?